INVOLVEMENT OF BUSINESS REPRESENTATIVES IN EDUCATIONAL ACTIVITIES OF UNIVERSITIES: PROBLEMS AND SOLUTIONS - S. Yu. Naumov; L. V. Konstantinova (Высшее образование в России)
The paper considers the issues of attracting business representatives to educational activities of higher educational institutions in the context of the improvement of the quality of higher education and personnel development of small and medium-sized businesses. The paper determines the required institutional mechanisms ensuring interaction of business representatives with higher educational institutions. These mechanisms include regulatory framework and organizational conditions. The authors identify the main problems that prevent the full use of normatively established opportunities for attracting business representatives to educational activities. The article formulates the problem-solving proposals for these challenges based on the experience of the higher educational institution represented by the authors, as well as the opportunities for participation of public associations of employers, in particular the Chamber of Commerce and Industry of the Russian Federation.